Regulation of Fumonisin B(1) Biosynthesis and Conidiation in Fusarium verticillioides by a Cyclin-Like (C-Type) Gene, FCC1 - Shim, Won-Bo (American Society for Microbiology, 2001)
Fumonisins are a group of mycotoxins produced in corn kernels by the plant-pathogenic fungus Fusarium verticillioides. A mutant of the fungus, FT536, carrying a disrupted gene named FCC1 (for Fusarium cyclin C1) resulting in altered fumonisin B(1) biosynthesis was generated. FCC1 contains an open reading frame of 1,018 bp, with one intron, and encodes a putative 319-amino-acid polypeptide. This protein is similar to UME3 (also called SRB11 or SSN8), a cyclin C of Saccharomyces cerevisiae, and contains three conserved motifs: a cyclin box, a PEST-rich region, and a destruction box. Also similar to the case for C-type cyclins, FCC1 was constitutively expressed during growth. When strain FT536 was grown on corn kernels or on defined minimal medium at pH 6, conidiation was reduced and FUM5, the polyketide synthase gene involved in fumonisin B(1) biosynthesis, was not expressed. However, when the mutant was grown on a defined minimal medium at pH 3, conidiation was restored, and the blocks in expression of FUM5 and fumonisin B(1) production were suppressed. Our data suggest that FCC1 plays an important role in signal transduction regulating secondary metabolism (fumonisin biosynthesis) and fungal development (conidiation) in F. verticillioides.